2000
DOI: 10.1523/jneurosci.20-20-07716.2000
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin DepletionIn VivoInhibits the Branching of Olfactory Projection Neurons in the Lobster Deutocerebrum

Abstract: Serotonin depletion during embryogenesis has been shown previously to retard the growth of the olfactory and accessory lobes of the lobster deutocerebrum (Benton et al., 1997). The present study was undertaken to determine whether morphological changes in the interneurons innervating these lobes contribute to this growth retardation. We examined the effects of in vivo serotonin depletion using 5,7-dihydroxytryptamine (5,7-DHT) on the morphology of the olfactory projection neurons, one of two major classes of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 49 publications
2
40
0
Order By: Relevance
“…Further experiments showed that, although mature projection neurons are not serotonin-immunoreactive in lobsters (24,25), newborn olfactory projection neurons are transiently able to take up serotonin. This phenomenon may be related to the role serotonin plays in promoting the ingrowth of new projection neurons into the olfactory neuropils of lobsters (23) and͞or to the effects of serotonin on the regulation of neurogenesis that are reported here.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Further experiments showed that, although mature projection neurons are not serotonin-immunoreactive in lobsters (24,25), newborn olfactory projection neurons are transiently able to take up serotonin. This phenomenon may be related to the role serotonin plays in promoting the ingrowth of new projection neurons into the olfactory neuropils of lobsters (23) and͞or to the effects of serotonin on the regulation of neurogenesis that are reported here.…”
supporting
confidence: 52%
“…These results suggest that the proliferation, growth, or morphogenesis of the local and projection neurons may be affected by serotonin depletion. Dye-injection studies have shown that the differentiation of a subset of the olfactory projection neurons is indeed affected by serotonin depletion: ϳ14% of the projection neurons sampled in serotonin-depleted embryos send axons toward the lateral protocerebrum via the olfactory globular tract (OGT), as expected, but do not innervate the OLs or ALs, as in normal embryos (23). Hence, it would seem that serotonin depletion in vivo inhibits the branching of olfactory projection neurons in lobsters, suggesting that one of the functions of serotonin during normal development is to promote, directly or indirectly, the growth of these neurons into the olfactory lobe glomeruli and associated brain neuropils.…”
mentioning
confidence: 67%
“…Towards this end, we have examined serotonin and nitric oxide as possible endogenous modulators of neurogenesis. Various in vitro and in vivo studies have shown that increases in serotonin levels result in an upregulation of neurogenesis in both the MPZ and LPZ of juvenile clawed lobsters (Benton and Beltz 2001a;Beltz et al 2001) and that decreases inhibit the branching of newborn projection neurons (Sullivan et al 2000). Furthermore, brain serotonin levels are under circadian control (Wildt et al 2004).…”
Section: Serotonin and Nitric Oxidementioning
confidence: 99%
“…The OL glomeruli are sites of synaptic contact between the ORNs, olfactory projection neurons and several classes of local interneurons. In crayfish and lobsters, the latter two classes of neurons also innervate an additional glomerular neuropil, the accessory lobe (AL), which lies adjacent to the OL (Arbas et al 1988;Mellon and Alones 1994;Wachowiak et al 1996;Sullivan et al 2000;Beltz 2001a,b, 2005b). In contrast to the OL, which receives only primary olfactory inputs, the AL receives higher-order olfactory, visual and mechanosensory inputs Sullivan and Beltz 2005b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation